Analysis of Factors Associated with Low Birth Weight Events - Dinengsih, Sri; Hardiyati, Nur Rahmi; Lail, Nurul Husnul (Universitas Islam Lamongan, 2022)
Low birth weight (LBW) babies weighing less than 2500 grams have a general condition that they are smaller than normal birth weight babies. Infants with low birth weight are a major factor in increasing infant and child neonatal mortality, morbidity and disability and have a long-term impact on their lives in the future.The purpose of this study was to analyze the factors associated with the incidence of low birth weight at Aulia General Hospital, South Jakarta.The research method is an analytical survey design with a cross sectional approach. The sample was 64 patients who gave birth to mothers in the maternal care room at RSU Aulia, South Jakarta. Sampling using purposive sampling with a questionnaire. The analysis was carried out by using the chi square test.The results of the study from 64 mothers giving birth at RSU Aulia, South Jakarta, obtained 50% of low birth weight babies. Bivariate analysis obtained all variables age (p value 0.000), anemia (p value 0.001), knowledge (p value 0.024), hypertension (p value 0.002), and anxiety (p value 0.000) <0.05 were significantly related to birth weight. low.The conclusion is that mothers who are at risk, have anemia, have low knowledge, have a history of hypertension, and feel anxious are likely to experience low birth weight.Suggestions for pregnant women to pay attention to their pregnancy and the condition of the fetus through ANC visits to health workers..